"Oh, I just had it in my head": Promoting mathematical communications in early childhood. (September 2015) - Lee, Joohi
This article presents effective strategies for educators of young children to promote children's mathematical communications, which include think-aloud during individual work time, utilizing reasoning and proof questions, and questioning back to children.